(untitled) (Applied Biological Research, 2025)
Nanoparticles (1–100 nm) are increasingly explored for environmental and biomedical applications. In this study, silver nanoparticles (AgNPs) were synthesized using Trigonella foenum-graecum (fenugreek) seed extract as a natural reducing and capping agent. Phytochemicals such as flavonoids, saponins, and polyphenols facilitated efficient formation and long-term stabilization of AgNPs. The synthesis, confirmed by surface plasmon resonance with an absorption peak at 420 nm, was further characterized by FTIR, revealing functional groups (C=C, O-H/N-H) responsible for reduction and capping. The AgNPs demonstrated strong antimicrobial activity against E. coli (19 mm) and S. aureus (17 mm), with MIC values of 25–50 μg/mL. Antioxidant potential was confirmed by DPPH assay (IC₅₀ = 46 μg/mL), indicating potent radical scavenging activity. The nanoparticles exhibited high yield (>85%), 30-day stability, and resistance to agglomeration. Bioactivity profiling across varying concentrations (100, 75, 50, and 25%) highlighted dose-dependent responses. The results suggest that fenugreek-mediated AgNPs act through membrane disruption, ROS generation, and interference with microbial DNA/protein synthesis. This green synthesis approach underscores the multifunctionality and sustainability of fenugreek-based AgNPs as promising next-generation antimicrobial agents.